The Influence of Working Memory Load on Expectancy-Based Strategic Processes in the Stroop-Priming Task - Ortells, Juan J.; Álvarez, Dolores; Noguera, Carmen; Carmona, Encarna; de Fockert, Jan W. (Frontiers in Psychology, 2017)
The present study investigated whether a differential availability of cognitive control resources as a result of varying working memory load could affect the capacity for expectancy-based strategic actions. Participants performed a Stroop-priming task in which a prime word (GREEN or RED) was followed by a coloured target (red vs. green) that participants had to identify. The prime was incongruent or congruent with the target color on 80% and 20% of the trials, respectively, and participants were informed about the differential proportion of congruent vs. incongruent trials. This task was interleaved with a working memory (WM) task, such that the prime word was preceded by a sequence of either a same digit repeated five times (low load) or five different random digits (high load), which should be retained by participants. After two, three, or four Stroop trials, they had to decide whether or not a probe digit was a part of the memory set. The key finding was a significant interaction between prime-target congruency and working memory load: Whereas a strategy-dependent (reversed Stroop) effect was found under low WM load, a standard Stroop interference effect was observed under high WM load. These findings demonstrate that the availability of working memory is crucial for implementing expectancy-based strategic actions.